Attributed Contribution of Therapist’s Emotional Variables to Psychotherapeutic Effectiveness: A Preliminary Study - Romero-Moreno, Antonio; Paramio, Alberto; Cruces-Montes, Serafín; Zayas, Antonio; Guil, Rocío (Frontiers in Psychology, 2021)
Background: The aim of this paper is to analyse the degrees of responsibility for healing that psychotherapists attribute to a set of emotional variables of the therapist involved in the therapeutic process. Such variables, framed within the well-known common factors in psychotherapy, have been proven to be essential in making the therapeutic process effective, as has been shown by research in psychotherapy in recent decades. Method: Based on an extensive literature review, the responses from a sample of 69 psychotherapists to a tool created ad hoc are analysed to verify whether their attributions are in line with the results of said review. Results: The therapists have doubts about the factors responsible for psychotherapeutic effectiveness, as well as about the value of common variables, including those of an emotional nature. Conclusions: Discrepancies have thus been found between the conclusions reached by research on therapeutic processes and the statements made by the therapists studied. We also propose lines of research and courses of action to be followed.